Prevalence of malnutrition in a tertiary hospital in Turkey: overlooked subject? - Yasin Sahin; Ahmet Rauf Goktepe; Evrim Ozen (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Aims: The study evaluated children's nutritional status at the moment of hospitalization. Patients and Methods: The nutritional status of 113 hospitalized patients was retrospectively evaluated at the time of hospitalization in the Clinic of Pediatric Gastroenterology between May 2013 and November 2014. During hospitalization, height for age, weight for age, and weight for height z scores were calculated. Results: Of the 113 patients in the study, 58 were female and 55 were male; the mean age was 59.59 ± 61.73 months and 67.87 ± 60.99 months, respectively. According to the World Health Organization standards, 33 (29.2%) underweight patients, 17 (15.0%) patients with acute malnourishment, and 21  18.6%) patients with chronic malnourishment were detected. Based on weight for age data, 10 (8.8%) patients were severely malnourished, 22 (19.5%) patients were moderately malnourished, 27 (23.9%) patients were mildly malnourished, 40 (35.4) patients had normal weight, 8 (7.1%) patients were  overweight, and 6 (5.3%) patients were obese. According to the Water low classifi cation, 14 (12.4%) children were stunted, 6 (5.3%) children were wasted-stunted, and 15 (13.3%) children were wasted. Conclusion: High rates of malnutrition were detected in hospitalized patients, therefore nutritional status should be carefully assessed at the moment of hospitalization to reduce the mortality rate, and patients should be given immediate nutritional support. The early diagnosis of mild or moderate malnutrition, and the timely start of treatment, will diminish the progression to severe malnutrition in developing countries like Turkey.